TINJAUAN HUKUM POSITIF DAN HUKUM ISLAM TERHADAP FENOMENA SOUND HOREG DALAM MENJAGA KETERTIBAN UMUM - Fawaid Abdullah Abbas; Raden Muyazin Arifin; Mohammad Arif Fauzi (LPPM Universitas Islam Ibrahimy Banyuwangi, 2025)
The phenomenon of sound horeg in Banyuwangi Regency is a cultural tradition that has evolved from the tradition of takbir keliling into an entertainment and social competition event using high-capacity sound systems that produce noise and strong vibrations. Despite providing social and economic benefits, sound horeg causes public disorder, public health issues, and property damage. This study uses a qualitative phenomenological method to examine the regulation of sound horeg from the perspective of positive law and Islamic law, as well as its impact on public order. Government regulations limit noise levels and the timing of implementation to control negative impacts, while Islamic law asserts that sound horeg is haram if it causes danger, damage, and disruption of worship, based on the principles of maqasid sharia. Legal responsibility is not only attached to the perpetrators and organizers but also to the government as the issuing authority. The research results emphasize the need for balanced management between cultural preservation and the protection of community rights to create harmonious order. Policy recommendations suggest integrating aspects of positive law and Islamic law with the collective awareness of all parties to maintain the common good.